Earnings management in family versus non-family firms: the influence of analyst coverage - Paiva, I. S.; Lourenço, I. C.; Curto, J. D. (Revista Española de Financiación y Contabilidad - Spanish Journal of Finance and Accounting, 2019)
This study investigates the relationship between the level of earnings management in family and non-family firms, and analyses whether or not this relationship depends on the level of monitoring effect from analysts. The empirical study relies on a sample of 1,043 UK listed firms. We find that family firms have higher levels of earnings management as compared to non-family firms, unless they are followed by a significant number of analysts. This study fills a gap in the literature by suggesting that not all family firms should be considered the same when addressing incentives for earnings management. It also highlights the moderator effect of the analyst coverage in the relationship between the family status and earnings management.